Role of plant growth-promoting bacteria on Phytoextraction process of Cu(II) and Cr(VI) by Helianthus annuus and Zea mays (2011)
As a result of inappropriate deposition of organic residues, toxic anthropogenic compounds have become ubiquitous components in soil and waters. Several alternatives have been developed, however, one of the most important is bioremediation. It is a low-cost, effective and environmentally friendly alternative to remediate contaminated soil. In particular, the phytoremediation of heavy metals has become an important tool to alleviate the impact occasioned by inorganic contamination with arsenic, lead, cadmium, copper or chromium, for example. We decided to evaluate the process of phytoextraction of copper by its implications in agricultural productivity and chromium by its negative effects on both human and animal health. Additionally, selected two vegetable species: maize and sunflower. With regard to maize, it is plant specie of fast-growth and high biomass, characteristics desired in a phytoremediation process. While sunflower has been widely reported and characterized by its qualities to extract several heavy metals from soil. Plant growth-promoting bacteria (PGPB) defined as microorganisms with beneficial effect on plant development, have elucidated to be a relevant strategy to improve phytoremediation process. In this study, we exhibited the role of PGPB on improvement of this biotechnological strategy. We evaluated eight bacteria and characterized them by its capacity as PGPR. Also, identified this molecularly. We demonstrated that bacterial inoculation with bacteria Pseudomonas putida GN4 and Acinetobacter sp. CC30 enhanced plant growth and the content of chlorophyll a, chlorophyll b and carotenoids in both maize and sunflower plants under copper (II) and chromium (VI) contamination. With respect to extraction process, bacterial inoculation exerted an important effect on ions mobility in soil. Furthermore, increased the availability of copper extractable from soil. Several bacterial strategies are though to influence the efficiency of phytoremediation process. Bacterial capacities to synthesize indole or siderophores, solubilize phosphate or mineralize ammonia have evidenced to influence significantly on remediation of heavy metals by plants. Hence, in summary, utilization of PGPR to improve phytoremediation process is an important alternative to reduce cost and increased remediation efficiency. Further, it is a sustainable strategy to preserve the quality of environment.